Humoral immune response in adult Brazilian patients with Mucolipidosis III gamma - Sperb-Ludwig, Fernanda (Genet Mol Biol, 2019)
Mucolipidosis II and III (ML II and III) alpha/beta and ML III gamma are lysosomal diseases caused by GlcNAc-1-phosphotransferase deficiency. Previous data indicate that MLII patients have functionally impaired immune system that contributes to predisposition to infections.We evaluated the immunological phenotype of three Brazilian patients with ML III gamma. Our data suggest that the residual activity of GlcNAc-1-phosphotransferase in patients with ML III gamma is enough to allow the targeting of the lysosomal enzymes required for B-cell functions maintenance.